2017
DOI: 10.1002/clen.201600635
|View full text |Cite
|
Sign up to set email alerts
|

Leaching of Phosphorus and Cadmium in Soils Amended with Different Bone Chars

Abstract: The benefits of bone char (BC) application may include both the mobilization of P for plant nutrition and immobilization of contaminant Cd in the soil. However, previous studies were conducted under equilibrium conditions that do not adequately reflect field conditions. Therefore, the objective was to study the effect of BC, surface-modified BC (BC plus ) and sulfur-enriched activated char (AC S ) application at different particle sizes on P-and Cd-mobilization under non-equilibrium conditions in a combined in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 53 publications
6
6
0
Order By: Relevance
“…This is consistent with the study of according to which the BC application (< 90 µm BC thoroughly mixed in soil) significantly increased the insoluble P proportion (H 2 SO 4 -P). Additionally, our study confirmed previous findings concerning the effect of particle sizes on the P release from BCs (Morshedizad and Leinweber, 2017) and consequently the P status of treated soils (Ma and Matsunaka, 2013). Sequentially extracted P contents increased with the decreasing size of BC particles whereby BC plus treatments appeared more dependent on particle size than BC treatments.…”
Section: P Availability As Revealed By Sequential Fractionationsupporting
confidence: 90%
See 4 more Smart Citations
“…This is consistent with the study of according to which the BC application (< 90 µm BC thoroughly mixed in soil) significantly increased the insoluble P proportion (H 2 SO 4 -P). Additionally, our study confirmed previous findings concerning the effect of particle sizes on the P release from BCs (Morshedizad and Leinweber, 2017) and consequently the P status of treated soils (Ma and Matsunaka, 2013). Sequentially extracted P contents increased with the decreasing size of BC particles whereby BC plus treatments appeared more dependent on particle size than BC treatments.…”
Section: P Availability As Revealed By Sequential Fractionationsupporting
confidence: 90%
“…These results imply that considerable changes in P speciation were more attributed to pH reductions, and accordingly leaching losses of solubilized P forms compared with P enrichment by BC plus dissolution. This is supported by results from a previous publication in which two particle sizes of BC plus gave a significant rise in the leached P concentration after 1, 5, 13, 34 and 70 days of incubation along with reductions in soil pH (Morshedizad and Leinweber, 2017). This is in line with Sato et al (2005) who found that increasing soil pH in a naturally acidic soil (pH = 4.32) was an effective approach to minimize P leaching, while pH decrease resulted in the transformation of stable to soluble and more leachable P species.…”
Section: P Speciation Of Treated Soils By Xanessupporting
confidence: 86%
See 3 more Smart Citations